2005
DOI: 10.1111/j.1528-1167.2005.22705.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of the Ketogenic Diet in Pediatric Epilepsy: Effects of Valproate Combination Therapy

Abstract: Summary:Purpose: To evaluate safety and tolerability of ketogenic diet (KGD) and valproate (VPA) cotherapy in the treatment of intractable seizures.Methods: The patient records of children who underwent KGD initiation at the Massachusetts General Hospital for Children from February 2002 to September 2004 were retrospectively assessed. Efficacy was measured by comparing reported seizure frequency at baseline and at 3-month intervals thereafter. Adverse events and reasons for terminating the diet were tabulated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 27 publications
(51 reference statements)
1
32
0
1
Order By: Relevance
“…In the administration of the KD, various complications occurred, but most were transient and could easily be managed by conservative treatments. 13,19 Even serious complications could be resolved after stopping the diet. 13 Contrary to the complications of diet therapy, we experienced sustained hemiparesis in 3 patients who had hemispherec(o)tomy.…”
Section: Discussionmentioning
confidence: 99%
“…In the administration of the KD, various complications occurred, but most were transient and could easily be managed by conservative treatments. 13,19 Even serious complications could be resolved after stopping the diet. 13 Contrary to the complications of diet therapy, we experienced sustained hemiparesis in 3 patients who had hemispherec(o)tomy.…”
Section: Discussionmentioning
confidence: 99%
“…Volume restriction or depletion during acute illness heightens the risk of urolithiasis by concentrating the urine and its stone-forming solutes. Within the past decade, renal calculi have been reported in 1.4—8.7% of children on the KD (Freeman et al, 1998; Hassan et al, 1999; Furth et al, 2000; Maydell et al, 2001; Nordli et al, 2001; Kossoff et al, 2002a,b; Vaisleib et al, 2004; Sampath et al, 2007) and hematuria in as many as 10% (Lyczkowski et al, 2005). In general, lower rates are reported when GU imaging is restricted to patients with pain or macroscopic hematuria, whereas higher rates of urolithiasis are detected when imaging is also performed in cases of occult hematuria or hypercalciuric hypocitraturia.…”
Section: Introductionmentioning
confidence: 99%
“…In the study that was done by Lyczkowski et al, 2 patients who took KD and VPA concomitantly experienced raises of the serum liver function enzymes (14). In 1 patient after 3 weeks, the serum levels of ALT and AST were increased to 201 U/L and 161 U/L, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The 2nd patient experienced the elevation of liver function tests after 2 weeks on the diet (ALT, 229 U/L; AST, 238 U/L). Albeit, after comparison of the adverse effects of patients who got the combination of KD and VPA and the patients who took exclusively KD, they concluded that concomitant introduction of KD and VPA did not increase the chance of hepatotoxicity (14). In addition, Ballaban-Gil et al reported 2 cases that had the marked elevation of liver function biomarkers during initiation of the diet and 13 months after commencement of KD (15).…”
Section: Discussionmentioning
confidence: 99%